2017
DOI: 10.3390/su9030470
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Productivity Growth and the Role of Capital in South Asia (1980–2013)

Abstract: Abstract:The study assessed agricultural sustainability in South Asia (i.e., Bangladesh, Pakistan, India and Nepal) by computing multi-lateral multi-temporal Total Factor Productivity (TFP) indices and their six finer components (technical change, technical-, scale-and mix-efficiency changes, residual scale and residual mix-efficiency changes) and examined the role of capital in driving TFP growth covering a 34-year period . Results revealed that all countries sustained agricultural productivity growth at vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 71 publications
5
55
0
Order By: Relevance
“…For instance, in South Asia, the major drivers of agricultural TFP growth were the levels of natural, human and technology capital endowments. In contrast, financial capital and crop diversification had opposite effects on TFP (Anik et al 2017). On the other hand, the TFP growth in Czech depended rather on natural and weather conditions (Macheck and Spicka 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in South Asia, the major drivers of agricultural TFP growth were the levels of natural, human and technology capital endowments. In contrast, financial capital and crop diversification had opposite effects on TFP (Anik et al 2017). On the other hand, the TFP growth in Czech depended rather on natural and weather conditions (Macheck and Spicka 2013).…”
Section: Discussionmentioning
confidence: 99%
“…due to technological progress at 4.7% and declined in technical efficiency at 1.9%. Anik et al (2017) observed the positive TFP growth rate of Bangladesh with a similar growth pattern of residual scale and mix efficiency change but they experienced no change in technical scale and mix efficiency for the period of 1980-2013. Table 3 shows that the increase in TFP index has not been uniform and fluctuation has occurred from year to year.…”
Section: Ranking Of Regions With Regard To Tfp Growth After Correctiomentioning
confidence: 79%
“…Additionally, research conducted by Kusnadi et al, (2016), Nwaru & Iheke (2010), and studies conducted by Yoko et al, (2017) states that land is an elastic variable in influencing rice production. Research conducted by Anik et al, (2017)The variable natural capital, labor, and technology is the main drivers in increasing the technical efficiency of rice production.…”
Section: Rice Production Frontiers In East Javamentioning
confidence: 99%
“…Certain relevant variables besides land that has a major impact on the technical efficiency of rice production based on research carried out by Anik et al, (2017) are the variables of natural resources, labor and technology. Another case with a study by Fuglie et al, (2017) notes that the key drivers of increased rice production are funding and development assistance from the government and the institutions concerned.…”
Section: Introductionmentioning
confidence: 99%